PENGEMBANGAN MODUL BIOINDIKATOR UNTUK MENINGKATKAN CAPAIAN KOMPETENSI MAHASISWA UNIVERSITAS ISLAM JEMBER - Umi Nurjanah; Ibrohim -; Dahlia - (JURNAL BIOSHELL, 2016)
The module is required to achieve optimal learning. This study aims to produce products such as bioindicator module that is valid for students of the Islamic University of Jember. This study refers to the model of development of the 4-D (Define, Design, Develop, Disseminate) which is limited only up to the stage-3. Module design is the result of research on bioindicators macrobenthos in Bedadung River and literature studies. The validity of the module is analyzed through expert validation sheet material, media experts and legibility students. Validation of subject matter experts score was 90.91%, from media experts score was 93.75% and legibility of student test score was 85, 38%. In conclusion bioindicator modules developed after the validation and revision declared eligible to be used as supplementary teaching materials Animal Ecology courses for student of Islamic University of Jember. Keywords: Module bioindicators, Students of Islamic University of Jember.